Cerebrospinal fluid biomarkers and apolipoprotein E genotype in cerebral amyloid angiopathy. A narrative review - Aikaterini Theodorou; Ioanna Tsantzali; Elisabeth Kapaki; Vasilios C. Constantinides; Konstantinos Voumvourakis; Georgios Tsivgoulis; George P. Paraskevas (Cerebral Circulation - Cognition and Behavior, 2021)
Sporadic cerebral amyloid angiopathy (CAA) is a cerebral small vessel disease, characterized by the deposition of β-amyloid within the cortical and leptomeningeal blood vessel walls. It has attracted interest concerning new therapeutic perspectives. However, there are scarce data regarding the cerebrospinal fluid biomarkers (CSF) and genetic factors in sporadic CAA.In this narrative review, we investigated the literature regarding the cerebrospinal fluid core biomarkers profile of patients with probable or possible CAA and its subtype, the CAA- related inflammation (CAA-ri), taking into account the clinical and radiological characteristics of the patients. We also analyzed the Apolipoprotein E (APOE) genotype differentiations among the different subtypes of cerebral amyloid angiopathy.Our results demonstrate specific CSF patterns of β-amyloid (Aβ42 and Aβ40) and tau-proteins (t-tau and p-tau) which may serve as molecular biomarkers for CAA/ CAA-ri and could prove helpful for novel therapeutic procedures. Specifically, decreased levels of Aβ40 and Aβ42 in both CAA and CAA-ri, mildly increased concentrations of tau protein in patients with CAA-ri and a strong association between APOE ε4/ε4 genotype and CAA-ri are the main findings.